PENGARUH PROSES PRODUKSI TERHADAP PEMASARAN KERUPUK DI DESA BABADAN KECAMATAN PANGKUR KABUPATEN NGAWI TAHUN 2009/2011 - Pujianto Pujianto (Universitas PGRI Madiun, 2013)
Agus cracker factory in the village of Babadan show lack of broader marketing. This is due to the lack of optimal production processes and equipment labour making process that affect the marketing of crackers. So that there was influence of the Produc- tion Process Of Marketing cracker in the Village District Babadan pickaxe Ngawi Re- gency Year 2009/2011. This study aims to determine the effect of the production process to marketing cracker in the Village District Babadan pickaxe Ngawi Regency Year 2009/2011. In this researh using survey methods this can be seen through title research to determine the effect between variables. The sample in this study using the technique of saturated samples sampling technique when all members of the population are used as samples. Collecting data using secondary data. In analyzing the data using a simple re- gression analysis and t-test. The results of analyses of data all the production process (X I) to marketing (Y) shows tcount for 2635> ttable of 2.032. He means acceptable means there is the influence of the production process to marketing. If the production increased by 1 % as well as the marketing will increase 0.597%, while the other factors being equal. In addition to the value obtained for the regression equation are value for R2. From the test results on the effects of the production process F (X I) to marketing (Y) shows the test results above it can be seen that the value of Fcount 6.943 >= Ftable. Of 3.286 at a signifi- cance level of 0.05. This means that the Ha accepted, meaning that the production pro- cess affects the marketing of crackers in the village district Babadan pickaxe years 2009-2011. Moreover. it can be said that there is a linear relationship between the production to marketing. From the results of this study concluded that tbere was an effect of the pro- duction process to the marketing of crackers in the Village District Babadan pickaxe Ngawi Regency Year 2009/2011. This is demonstrated by the acquisition of the data analysis.